2017
DOI: 10.20334/2017-054-m
|View full text |Cite
|
Sign up to set email alerts
|

Performance Investigation of Data Packets Transport Control Protocol in Heterogeneous Networks

Abstract: Disertacija rengta 2010-2017 metais Vilniaus Gedimino technikos universitete. Vadovas prof. dr. Šarūnas PAULIKAS (Vilniaus Gedimino technikos universitetas, elektros ir elektronikos inžinerija-01T). Vilniaus Gedimino technikos universiteto Elektros ir elektronikos inžinerijos mokslo krypties disertacijos gynimo taryba: Pirmininkas prof. dr. Dalius NAVAKAUSKAS (Vilniaus Gedimino technikos universitetas, elektros ir elektronikos inžinerija-01T). Nariai: doc. dr. Lina NARBUTAITĖ (Kauno technologijos universitetas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 48 publications
(67 reference statements)
0
0
0
Order By: Relevance
“…Such an ACK optimization concept has been proposed by authors in [25] and summarized in [26] as shown in Figure 1. In the beginning, to avoid the activation of ACK rate limiting or to disable it after data packet loss or retransmission, the kernel tracks the TCP session status.…”
Section: Tcp Acknowledgment Mechanism In Linux Kernelmentioning
confidence: 99%
“…Such an ACK optimization concept has been proposed by authors in [25] and summarized in [26] as shown in Figure 1. In the beginning, to avoid the activation of ACK rate limiting or to disable it after data packet loss or retransmission, the kernel tracks the TCP session status.…”
Section: Tcp Acknowledgment Mechanism In Linux Kernelmentioning
confidence: 99%